Electronic structures and ferromagnetism of 3C-SiC doped with (Fe, Co) double-impurities by first-principles calculations. (July 2021) - Lin, Long; Chen, Yujin; Tao, Hualong; Yao, Linwei; Huang, Jingtao; Lou, Mengsi; Chen, Ruixin; Yan, Longbin
Abstract: The magnetic and optical properties of pure, Fe, Co mono-doped and (Fe, Co) co-doped 3C-SiC were estimated, respectively, by using the plane wave pseudopotential method, with the first-principles of density functional theory. The calculation results show that pure 3C-SiC is non-magnetic semiconductor. The Fe, Co mono-doped and (Fe, Co) co-doped 3C-SiC exist spin-polarized and magnetic. The results of magnetization energy for (Fe, Co) co-doped 3C-SiC indicate the system exist FM coupling. From the imaginary part of the dielectric function and the absorption spectrum, it is found that the concentration of excited electrons in (Fe, Co) co-doped 3C-SiC crystals is less than that in pure 3C-SiC and Fe, Co mono-doped 3C-SiC, while the concentration of pure 3C-SiC is the largest. Both the mono-doped and co-doped systems have red-shifted absorption edges, and the optical band gap is reduced. The peak of the pure 3C-SiC is larger than that of Fe, Co doped and (Fe, Co) co-doped 3C-SiC.